Pelatihan Pembuatan Sabun Limbah Minyak Jelantah Proses Saponifikasi Pemberdayaan Masyarakat Pesisir Hamparan Perak Medan Belawan - Nyimas Yanqoritha; Al Muhyi, Ade; Rahmadia, Nirma; Siska, Siska; Gunawan, Muhammad Rizky (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Used cooking oil waste is often disposed of incorrectly, contributing to water and soil pollution and health risks if not managed properly. Training on making soap from used cooking oil in coastal communities, emphasizing environmental sustainability and economic empowerment. Participants gain practical skills, which lead to business opportunities. This activity was carried out on October 23, 2024, targeting housewives from Fisherman's Village, Hamparan Perak, Medan Belawan. Understanding indicators are evaluated using the questionnaire instrument. This output follows the target, namely obtaining a product that is made simply, at low cost, and affordable. The results of monitoring the increase in public understanding from the pre-test questionnaire and post-test showed that the participants strongly agreed (SA1) 75%, while the post-test strongly agreed (SA2) 85%, agreed (A2) 15%, that the theme of the activity was by the participants' needs. This shows that the choice of activity theme is appropriate and in line with the needs of the Hamparan Perak fishing village community, namely to manage used cooking oil kitchen waste into soap products that are useful and economical, as well as protecting the surrounding environmental resources, namely water and land, the community also contributes to sustainable practices and environmental health.